Blood pressure and kidney outcomes in patients with severely decreased glomerular filtration rate: a nationwide observational cohort study. Issue 8 (21st August 2022) - Al-Sodany, Ehab; Chesnaye, Nicholas C.; Heimbürger, Olof; Jager, Kitty J.; Bárány, Peter; Evans, Marie
Abstract : Objectives: To investigate the association between blood pressure (BP) and kidney outcomes in patients with estimated glomerular filtration rate less than 30 ml/min per 1.73 m 2 and different degrees of albuminuria. Methods: National observational cohort study of 18 071 chronic kidney disease (CKD) stage 4–5 patients in routine nephrology care 2010–2017. The association between both baseline and repeated clinic office BP and eGFR slope and kidney replacement therapy (KRT) was explored using multivariable adjusted joint models. The analyses were stratified on albuminuria at baseline. Results: The adjusted yearly eGFR slope became increasingly steeper from −0, 91 (95% CI −0.83 to −1.05) ml/min per 1.73 m 2 per year in those with SBP less than 120 mmHg at baseline to −2.09 (−1.83 to −2.37) ml/min per 1.73 m 2 in those with BP greater than 160 mmHg. Similarly, eGFR slope was steeper with higher DBP. Lower SBP and DBP was associated with slower eGFR decline in patients with albuminuria grade A3 (>30 mg/mmol) but not consistently in albuminuria A1–A2. Those with diabetes progressed faster and the association between BP and eGFR slope was stronger. In repeated BP measurement analyses, every 10 mmHg higher SBP over time was associated with 39% additional risk of KRT. Conclusion: In people with eGFR less than 30 ml/min per 1.73 m 2, lower clinic office BP is associated with more favorable kidney outcomes. Our results support lower BP targets also in people with CKD stage 4–5.